Meccan and Madani (Islamic Sciences Journal, 2023)
One of the main features of Islamic law is that it has revealed gradually. So the Qur’anic verses are revealed to the greatest messenger, our master Muhammad (peace and blessings of God be upon him), keeping pace with the progress of the Islamic society, advising it, correcting its path, legislating the rules necessary for its integrity.The Prophet’s migration was considered as a fundamental difference between two different stages of the Islamic call, and that migration shapes also a difference between two types of the Holy Qur’an, namely the Meccan Qur’an and the civil Qur’an.Hence, it lies that the Meccan and the Madani are an important foundation and pillar in understanding the history of Islamic legislation, knowing the retracted and abrogated, the reasons for revelation, etc..